Cutaneous Lesions Presenting as Recurrent Annular Erythema in a Child with Juvenile Myelomonocytic Leukemia, Coeliac Disease, and CALMs: The Myriad Manifestations of RASopathy - Bishnupriya Sahoo; Shikhar Ganjoo; Mohinder Pal Singh Sawhney; Seema Nagger (Wolters Kluwer Medknow Publications, 2021)
In neurofibromatosis type 1 (NF-1), a Ras-pathway mutation disorder both celiac disease and juvenile myelomonocytic leukemia (JMML) have been found in association. A 3-year-old male child presented to us with annular erythema and cafe-au-lait macules (>6 in number). On investigation, he was found to have JMML and celiac disease. A child with early manifestation of NF1 in association with JMML and celiac disease is an even rarer presentation.